1998
DOI: 10.1557/jmr.1998.0347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nanoparticles on the Structure and Crystallization of Amorphous Silicon Thin Films Produced by rf Glow Discharge

Abstract: Thin films of nanostructured silicon (ns-Si : H) were deposited by plasma-enhanced chemical vapor deposition in the presence of silicon nanoparticles at 100 ± C substrate temperature using a silane and hydrogen gas mixture under continuous wave (cw) plasma conditions. The nanostructure of the films has been demonstrated by diverse ways: transmission electron microscopy, Raman spectroscopy, and x-ray diffraction, which have shown the presence of ordered silicon clusters (1-2 nm) embedded in an amorphous silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
(22 reference statements)
2
23
0
Order By: Relevance
“…The lattice constant deduced from this diffraction pattern is 3.7 Å. A similar crystalline structure was found in nanostructured Si thin films deposited under continuous SiH 4 -H 2 rf plasma 12 and in Si nanometric powder, 22 where nanocrystalline clusters with fcc structure were found to be embedded in an amorphous matrix. It is assumed that polymorphous Si films are formed by the incorporation of Si nanocrystallites ͑grown in the plasma gas phase͒ in an amorphous Si film.…”
Section: A Tem Characterizationsupporting
confidence: 74%
See 2 more Smart Citations
“…The lattice constant deduced from this diffraction pattern is 3.7 Å. A similar crystalline structure was found in nanostructured Si thin films deposited under continuous SiH 4 -H 2 rf plasma 12 and in Si nanometric powder, 22 where nanocrystalline clusters with fcc structure were found to be embedded in an amorphous matrix. It is assumed that polymorphous Si films are formed by the incorporation of Si nanocrystallites ͑grown in the plasma gas phase͒ in an amorphous Si film.…”
Section: A Tem Characterizationsupporting
confidence: 74%
“…5 Recently, silicon films deposited under conditions close to those for powder-particle formation have revealed interesting new optoelectronic properties, in particular better transport and stability properties as compared to a-Si:H. [6][7][8][9] This new class of silicon thin films has been fabricated using a wide range of plasma conditions. [10][11][12][13][14] They are referred to as polymorphous silicon ͑pm-Si:H͒.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to previous crystallization experiments carried out at a lower temperature (590°C) during isothermal treatments, where pm-Si:H crystallized faster than a-Si:H did. 16 In that case, nucleation was heterogeneous, and the grain size after crystallization was correlated with the density of nanoparticles revealed by transmission electron microscopy. This apparent contradiction could be understood if we take into account the pronounced dependence of the homogeneous nucleation rate r n on temperature.…”
Section: Crystallizationmentioning
confidence: 92%
“…A number of structural analyses have revealed that polymorphous silicon has a higher degree of medium-range order than the conventional amorphous material. 9,10 Both samples have been deposited onto the walls of the reaction chamber, which was maintained at 250°C during 10 h. This long deposition time results in thick layers of around 10 m. The third sample consists of hydrogenated silicon nanoparticles (np-Si:H). They were grown in a pure silane plasma at room temperature (for details see Ref.…”
Section: Lpicm (Umr 7647 Cnrs) Ecole Polytechnique 91128 Palaiseau Cmentioning
confidence: 99%